Dress to Impress: Exploring Clothing Mechanics and Gender Performance in Mobile Game Empress’s Choice - Adelia, Silvy; Ayu, Hujuala; Ariyanti, Lisetyo; Kusumadewi, Kenya; Arista, Cicik; Xin, Wang (Institut Seni Indonesia Denpasar, 2024)
This study investigates how game mechanics influence gender performance through clothing choices in Empress's Choice. The game was first launched on mobile devices, chromebook, and tablets in June 2022. Players would be able to enjoy the game on a variety of platforms. This study employs content analysis to explore game mechanics and in-game elements, specifically focusing on how they affect the players' construction of their characters' gender. The analysis is limited to chapters featuring dressing-up and destiny event stages, where clothing choices are central to gameplay. Judith Butler's theory of performativity is a framework to examine whether the game reinforces traditional gender norms or encourages players to subvert them. The findings reveal that, despite the game's emphasis on player choices, the mechanics, especially those related to clothing and its associated features, still largely adhere to conventional gender expectations. The main character (player) is constructed to be female by repeatedly donning feminine clothes in mostly bright colors and elaborate accessories. All categories of clothing (type, color, and accessories) in the game have a particular bias towards traditional feminine elements. Therefore, during dress-up stages, players have limited choices in gender expression besides the feminine style dictated by the mechanics. However, the in-game actions, part of destiny events, show a contrasting experience. These events give players choices that impact the story without imposing specific gendered behaviors. This complexity indicates that limitations and opportunities to challenge gender norms exist in Empress's Choice through its game mechanics.